“What should be done to achieve greater use of cloud computing by higher education institutions” - Alajmi, Qasim; Sadiq, Ali Safa (IEEE, 2016)
Cloud computing is a technology in which online service providers can store and host organizational data and information without the need for computer hard drives to be centered in organizations. The information is hosted on a network server where it can be accessed by enterprises and users when in need. Small and large companies, as well as institutions of higher learning, are embracing this technology due to economic advantage, improved manageability, less maintenance, high performance, accessibility/ availability thus bringing about a smooth facilitation of organizational operations [1]. The technology used in cloud computing is dependent on a reliable internet connection that may be unavailable in some countries and in certain business environments. There is a debate on the integrity, privacy, and ownership of the data hosted in a cloud computing scenario making it difficult for some organization to adopt this technology. Cloud computing poses privacy concerns because the security of data on this platform is available to a huge viewership making it susceptible to the ill-minded cyber criminals/hackers.